(untitled) (International Journal of Engineering and Computer Science, 2015)
The use of mobile devices, such as smart phones and cellular phones, in field data collection has increased recently due to the emergence of Global Position Systems (GPS) and Wi-Fi Internet access. Timely and handy field data collection is required for disaster management and quick response during emergencies. In this paper, we introduce a dynamic web-based system to collect the field data from personal mobile phones. The main objective of this work is to demonstrate a real-time field data collection method that can be used by Traffic Department. The purpose of this system is to allow the Traffic Police Officer to send the field collected data to the server. The information gathered using field data collection can include current location, IMEI number, phone number, license number and images captured during crime scene. The data at server side can then be used for analysis and decision making. The data captured from android will be shown on Google Maps using Google Maps API v3.This data will be available to corresponding departments of government through the web service.